Technical Analysis as a Method of Risk Management - Gregor Dorfleitner; Christian Klein (Universität Augsburg, Institut für Statistik und Mathematische Wirtschaftstheorie, 2003)
While the academic world is still discussing if charting works or if it is more or less something like "Voodoo finance", the practical orientated world has been using technical analysis for decades. One argument of practitioners is, that technical analysis is useful to "disciplinate" the trader and consequently is a method of risk reduction. We discuss this argument theoretically and empirically and show, that it is not always right.
Keywords: 330; Wertpapieranalyse; Börsenkurs; Volatilität; Risikomanagement; Schätzung; Welt